Nurses' challenges in caring for an organ donor brain dead patient and their solution strategies: A systematic review - Hamideh YazdiMoghaddam; Zahra-Sadat Manzari; Eesa Mohammadi (Wolters Kluwer Medknow Publications, 2020)
Background: Caring for brain dead patient is one of the most troublous duties of an Intensive Care Unit (ICU) nurse. This study aimed to determine nursing challenges based on recent literature and identify the strategies to overcome these challenges. Materials and Methods: In this systematic review, the standard systematic review guideline of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) was used with articles published in PubMed, Science Direct, Scientific Information Database (SID), and Google Scholar databases during 2000-2018 on the keywords "brain dead OR brain death" and "nurses OR nursing." After the primary search, 212 articles were found. Eventually, 21 articles were selected for the final evaluation. Results: According to the results, the challenges included the concept and diagnosis of brain death, religious, and cultural beliefs opposing organ donation, lack of knowledge about the care process, interactions with the families. The proposed strategies were providing medical and nursing interventions to maintain a brain dead patient for organ donation, providing working conditions that maintain nurses' health, and increase the quality of care. Conclusions: Nurses play an important role in the care process of brain dead patients; therefore, recognizing their challenges can be the first step in increasing holistic care and maintaining organ vitality for transplantation. It is suggested that nursing authorities commence special educational programs with the aim to increase the knowledge of nurses about the care process of brain dead patients.